[¹⁸F]MK-9470, a positron emission tomography (PET) tracer for in vivo human PET brain imaging of the cannabinoid-1 receptor - Burns, H. Donald; Van Laere, Koen; Sanabria-Bohórquez, Sandra; Hamill, Terence G; Bormans, Guy; Eng, Wai-si; Gibson, Ray; Ryan, Christine; Connolly, Brett; Patel, Shil; Krause, Stephen; Vanko, Amy; et al. (Proceedings of the National Academy of Sciences - PNAS, 2007)
[¹⁸F]MK-9470 is a selective, high-affinity, inverse agonist (human IC₅₀, 0.7 nM) for the cannabinoid CB1 receptor (CB1R) that has been developed for use in human brain imaging. Autoradiographic studies in rhesus monkey brain showed that [¹⁸F]MK-9470 binding is aligned with the reported distribution of CB1 receptors with high specific binding in the cerebral cortex, cerebellum, caudate/putamen, globus pallidus, substantia nigra, and hippocampus. Positron emission tomography (PET) imaging studies in rhesus monkeys showed high brain uptake and a distribution pattern generally consistent with that seen in the autoradiographic studies. Uptake was blocked by pretreatment with a potent CB1 inverse agonist, MK-0364. The ratio of total to nonspecific binding in putamen was 4-5:1, indicative of a strong specific signal that was confirmed to be reversible via displacement studies with MK-0364. Baseline PET imaging studies in human research subject demonstrated behavior of [¹⁸F]MK-9470 very similar to that seen in monkeys, with very good test-retest variability (7%). Proof of concept studies in healthy young male human subjects showed that MK-0364, given orally, produced a dose-related reduction in [¹⁸F]MK-9470 binding reflecting CB1R receptor occupancy by the drug. Thus, [¹⁸F]MK-9470 has the potential to be a valuable, noninvasive research tool for the in vivo study of CB1R biology and pharmacology in a variety of neuropsychiatric disorders in humans. In addition, it allows demonstration of target engagement and noninvasive dose-occupancy studies to aid in dose selection for clinical trials of CB1R inverse agonists.